Environmental refuges from disease in host–parasite interactions under global change. Issue 4 (28th February 2023) - Gsell, Alena S.; Biere, Arjen; de Boer, Wietse; de Bruijn, Irene; Eichhorn, Götz; Frenken, Thijs; Geisen, Stefan; van der Jeugd, Henk; Mason‐Jones, Kyle; Meisner, Annelein; Thakur, Madhav P.; van Donk, Ellen; et al.
Abstract: The physiological performance of organisms depends on their environmental context, resulting in performance–response curves along environmental gradients. Parasite performance–response curves are generally expected to be broader than those of their hosts due to shorter generation times and hence faster adaptation. However, certain environmental conditions may limit parasite performance more than that of the host, thereby providing an environmental refuge from disease. Thermal disease refuges have been extensively studied in response to climate warming, but other environmental factors may also provide environmental disease refuges which, in turn, respond to global change. Here, we (1) showcase laboratory and natural examples of refuges from parasites along various environmental gradients, and (2) provide hypotheses on how global environmental change may affect these refuges. We strive to synthesize knowledge on potential environmental disease refuges along different environmental gradients including salinity and nutrients, in both natural and food‐production systems. Although scaling up from single host–parasite relationships along one environmental gradient to their interaction outcome in the full complexity of natural environments remains difficult, integrating host and parasite performance–response can serve to formulate testable hypotheses about the variability in parasitism outcomes and the occurrence of environmental disease refuges under current and future environmental conditions.